An experimental study of noise reduction of portable generator using local made acoustic enclosure - 1dalal9 kareem; Abbas J. Jubear; Hussain R. Al-Bugharbee (Wasit Journal of Engineering Sciences)
Portable generators are now widely used in shops, offices, and homes to provide electrical power during power outages in Iraq. However, these generators produce a lot of noise emitted from rotating mechanical parts and fuel combustion inside engine chamber. This noise has a negative impact on the neuroendocrine, cardiovascular, respiratory, and digestive systems. The reduction of generator noise still attracts the interest of many researchers. In this work, the reduction of generator noise under the use of an acoustic enclosure, made from local materials, is investigated experimentally. Experimental work is conducted using a 2kW generator and compares the sound intensity for two cases: a generator without enclosure and one with enclosure. The enclosure is made from plywood, galvanized sheet, glass wool, cork, and a compressed sponge.  The results include the measurement of sound intensity at day and night, at zero to full load, and at two different distances. The findings depicted that generator noise reduction reaches 10.3 dB at night and 9.6 dB during the day. In addition, the engine temperature, in case of using the enclosure, is kept within the allowable range of air-cooled generators which is 300 °C.  The maximum temperature at 100% load measured inside the enclosure was 77.86 °C during the night time and 91.75 °C at day time.